IMproving BMICG Group Sales Performance by Optimizing Human Resources Contribution (PT Mitra Cipta Kreatika - BMICG) - Leony, Augustine; Ros Bangun, Yuni (The Indonesian Journal of Business Administration, 2017)
Abstract – The economic crisis happened since early of 2014, has impacted the sales performance of service business companies in Indonesia. The growth of creative service business is rapidly increasing; there are approximately 700 creative service business companies across Indonesia by 2015.